Why are Macroeconomic Imbalances so Important for the European Monetary Union? - Roberto Tamborini (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2017)
According to a well established view of the crisis in the European Monetary Union (EMU), its seeds were planted well before the world financial collapse of 2007-08 and the subsequent Great Recession. The seeds, "macroeconomic imbalances" in the Brussels language, lie in the lack of real convergence across member countries. The idea is that as long as countries are on divergent trajectories of growth of GDP, productivity and incomes, 1) large and unsustainable current account imbalances will also emerge, 2) the ensuing capital movements may suddenly stop triggering bank and financial crises, 3) national fiscal policies will also be put under pressure by the need to bailout faltering banking systems while countries on a low growth path will also face harder convergence towards the 60% debt target, with higher interest rates and heavier fiscal effort.The Commission is entirely devoted to pro-growth and convergence policies, and the surveillance on macroeconomic imbalances figures prominently among the new tools of European governance. Prof. Roberto Tamborini, Department of Economics and Management of the~University Trento (UdT is a network partner of EconPol Europe), says: "Formalising the convergence process is an important goal in the road map towards the completion~of Europe's Economic and Monetary Union. Higher growth across Europe is of course a valuable aim.~But are convergent, tendentially uniform, growth rates really a sine-qua-non condition in a monetary union? Is there any economic tendency towards this outcome? Are, otherwise, such calamities as 1), 2), and 3) inevitable?"
Keywords: 330